Moral Immemorial: The Rarity of Self‐Criticism for Previous Generations' Genocide or Mass Violence. (7th March 2013) - Leach, Colin Wayne; Zeineddine, Fouad Bou; Čehajić‐Clancy, Sabina
<x xml:space="preserve">Abstract</x> Partly in response to political leaders' public expressions of self‐criticism for past generations' genocide or other mass violence, psychologists have suggested that individuals who are psychologically connected to perpetrators may view themselves as sharing some responsibility. Such broadened self‐perception should enable self‐criticism for past failures just as it enables self‐congratulation for past triumphs. We review studies of self‐criticism regarding European colonization (of Africa, the Americas, Australia, and Indonesia) and 20th century genocide (in Bosnia, Germany, Norway, and Rwanda). Self‐criticism—feelings of guilt, shame, and responsibility; wanting reparation—tended to be low. Self‐criticism appeared to be lowest among nonstudent samples, those allowed to explicitly disagree with self‐criticism, and those asked about more recent violence. Theoretical and practical implications of these patterns are discussed.